Could the Mesoproterozoic Kyalla Formation Emerge as a Viable Gas Condensate Source Rock Reservor Play in the Beetaloo Sub-Basin?. Issue 1 (1st December 2018) - Altmann, Carl; Baruch, Elizabeth; Close, David; Faiz, Mohinudeen; Richards, Brenton; Cote, Alexander
Abstract : Reservoir and geomechanical analysis of Kyalla Formation core and wireline logs acquired at Beetaloo W-1 indicate the presence of two potential Source Rock Reservoir (SRR) intervals; the middle Kyalla SRR and the lower Kyalla SRR. The key properties of the SRRs include TOC 1-3%wt, PHUT 5-10%BV, SWT 30-60%PV, free gas porosity 2-5%BV, and 20-40scf/ton adsorbed gas content. A Poissons Ratio of 0.15-0.2 and Young's Modulus of 30-35GPa suggest favourable geomechanical properties for effective hydraulic fracture stimulation. The lower Kyalla SRR has the greatest potential as it displays consistently positive geomechanical properties over the entire SRR interval as well as consistently high free gas porosity (>2-3%BV). Mudgas and core analysis indicate that the reservoir hydrocarbon phase is likely to be a wet gas. Potential retrograde condensation may yield significant condensate and LPG fractions from the produced gas stream. The positive reservoir and geomechanical properties within the Kyalla Formation SRR intervals at Beetaloo W-1 suggest further appraisal work is warranted to determine the deliverability of the SRRs and to determine what LPG and Condensate yields can be recovered at the well head.